A genetic variant in the cytochrome P450 family 2 subfamily R member 1 determines response to vitamin D supplementation. Issue 2 (April 2019) - Bahrami, Afsane; Mehramiz, Mehrane; Ghayour-Mobarhan, Majid; Bahrami-Taghanaki, Hamidreza; Sadeghi Ardekani, Kiana; Tayefi, Maryam; Sadeghzade, Mahsa; Rashidmayvan, Mohammad; Safari Ghalezou, Maryam; Ferns, Gordon A.; Avan, Amir; Sadeghnia, Hamid Reza
Summary: Background: Globally, about 1 billion people have inadequate levels of serum vitamin D and it is prevalent in all ethnicities and age groups. Few foods naturally contain sufficient vitamin D; therefore, most people get their requirements through supplementation. Hence vitamin D status is affected by genetic and environmental determinants including season of measurement, diet habitual, health status, body mass index and concurrent medication. Further studies are necessary to understand how genetic variation influences vitamin D metabolism. We aimed to explore the association between a potential vitamin D-related polymorphism (the rs10766197 polymorphism in the CYP2R1 gene) with the response to supplementation of vitamin D in 253 healthy Iranian girls. Material and method: A total of 253 healthy subjects received 50, 000 IU of vitamin D3 weekly for 9 weeks. Serum 25(OH)D concentrations and metabolic profiles were measured at baseline and after 9 weeks of supplementation. The genotypes of the CYP2R1 variant (rs10766197) were identified using TaqMan genotyping assays. Results: Serum 25(OH)D during the supplementation, increased in all individuals. Subjects with a AA major genotype at this locus had higher vitamin D concentrations after intervention (Changes (%) 448.4% ± 425% in AA vs 382.7% ± 301% in GG). This genetic variant modulated the response to supplementation ( p  < 0.001 and p -value SNP = 0.05). Regression analysis showed that the probability of affecting serum 25(OH)D, in individuals who had homozygous major allele GG was two-fold higher than carriers of the uncommon allele A (OR = 2.1 (1–4.2); p = 0.03). Interestingly, the Hs-CRP was reduced in AA carries while was elevated in individuals with GG and AG genotypes, after high-dose vitamin D supplementation. Conclusion: Changes in serum vitamin D and metabolic profile following high dose supplementation with vitamin D were associated with CYP2R1 polymorphism. Although carriers of the common G allele showed a greater response in the serum vitamin D.